Secondary physiological pneumonectomy to bronchial tuberculosis - González, Ricardo Adolfo Zapata; Parra, Carolina Salinas; Rincón, Ricardo Andrés Torres (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
Tracheobronchial tuberculosis is a rare presentation of pulmonary tuberculosis, which can affect between 10–40% of patients with active pulmonary tuberculosis, however the low positivity of the samples in isolation of acid-fast bacilli joined with indistinguishable clinical and radiological findings of lung involvement makes the diagnosis of bronchial tuberculosis to be wrong or late. A case of tracheobronchial tuberculosis with secondary complete lung collapses to bronchial stenosis with rapid onset, which according to the literature review is an unusual severe sequel.